2022
DOI: 10.3389/fphar.2022.942955
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Serum Pharmacochemistry, Metabolomics, and Network Pharmacology to Reveal the Material Basis and Mechanism of Danggui Shaoyao San in the Treatment of Primary Dysmenorrhea

Abstract: Danggui Shaoyao San (DSS), a well-known formula, has been successfully applied in treating primary dysmenorrhea (PD) in China. However, its material basis and mechanism are still unrevealed. This current research aims to reveal the material basis and mechanism of DSS in treating PD by an integrative approach of serum pharmacochemistry, metabolomics, and network pharmacology. The results showed that DSS markedly relieved the physiological and pathological symptoms of PD as confirmed by the improvement of writhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…24 Several theories and strategies, including metabolomic, ngerprint, serum pharmacology/ pharmacochemical and network pharmacology, have also been developed, facilitating screening for potential active components and studying the cooperative functions of multiple TCM components. 17,25 Additionally, UPLC-MS can be used to assess small particles and high-pressure systems, allowing improved chromatographic resolution and more sensitive analysis in less time and at higher analytical speeds. Thus it has oen been applied for separating traces and complex compounds, becoming among the most efficient pharmaceutical analysis methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Several theories and strategies, including metabolomic, ngerprint, serum pharmacology/ pharmacochemical and network pharmacology, have also been developed, facilitating screening for potential active components and studying the cooperative functions of multiple TCM components. 17,25 Additionally, UPLC-MS can be used to assess small particles and high-pressure systems, allowing improved chromatographic resolution and more sensitive analysis in less time and at higher analytical speeds. Thus it has oen been applied for separating traces and complex compounds, becoming among the most efficient pharmaceutical analysis methods.…”
Section: Discussionmentioning
confidence: 99%
“…16 TCM serum pharmacochemistry can be used to screen for effective TCM substances from the compounds absorbed into blood after oral administration; this process can reveal drug absorption and metabolism, as well as drug interactions. 17 Network pharmacology is a prediction platform for constructing TCM component–disease–target networks based on big data, allowing investigators to comprehensively evaluate TCM effectiveness and mechanisms. 18…”
mentioning
confidence: 99%
“…However, recent studies have linked an increase in the pentose glucuronate interconversion with alterations in the microbiome of patients with mouth infections [31,32]. Further, pharmacological studies have reported that the effects of some anti-inflammatory agents are mediated through the modulation of this metabolic pathway in humans and experimental animals [33,34].…”
Section: Figurementioning
confidence: 99%
“…Currently, TCM has been widely used to treat gastrointestinal diseases [ 6 ], but the unknown material basis and pathways of action have seriously hindered its internationalization [ 7 ]. Serum pharmacochemistry aims to screen the efficacious substance matrix of TCM from the components absorbed into the blood after oral administration, reflecting the multi-component synergy for overall biological effects and has gained wide acceptance and application [ 8 ], but it does not involve the study of functional mechanisms, while network pharmacology can make up for the lack of serum pharmacochemistry by constructing complex biological networks in the organism and predicting the functional mechanisms during drug therapy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%